ANALISIS KONDUKTIVITAS HIDROLIK JENUH TANAH PADA BERBAGAI JENIS NAUNGAN DI LAHAN KOPI RAKYAT KECAMATAN SUMBERMANJING WETAN - Desya Wahyu Annisa; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Coffee plants are one of the plantation crops that are widely cultivated by smallholders in Sumbermanjing Wetan District. The problem that is often experienced by coffee farmers is the decline in coffee production due to climate. The adverse effect of climate change can be overcome through mitigation by implementing shade plants. The saturated hydraulic conductivity of the soil is defined as the movement of water in a porous medium in a saturated state. By measuring hydraulic conductivity, it can determine the ability of the soil to conduct water and see the movement of water in the soil. The highest value of saturated hydraulic conductivity at a depth of 0-20 cm was found in coffee plants with sengon shade at 31.02 cm hour-1. The highest value of saturated hydraulic conductivity at a depth of 20-40 cm was found in coffee plants with the shade of Dadap plants, which was 56.67 cm hour-1, included in the fast category. Differences in shade and soil depth in coffee fields affect the value of the saturated hydraulic conductivity. There is a relationship between several physical properties of the soil and the saturated hydraulic conductivity of the soil. The physical properties of the soil affect the saturated hydraulic conductivity of the soil.